Pembinaan sistem manajemen usaha keramba jaring apung melalui percontohan usaha - Irwan Effendi; Sri Wahyuni (Unri Conference Series: Community Engagement, 2019)
Floating cage (KJA) is one of the most intensive aquaculture activities carried out in the country and the number is increasing, including in the Koto Panjang Hydroelectric Lake, Kampar. In this area, this business has been started since 1995 and continues to grow rapidly and reaches its peak in 2010-2012. In the following years, the business began to be relatively stagnant and profits from entrepreneurs continued to decline. As a result, many entrepreneurs went bankrupt and closed businesses. With this background, the writer is interested in making a pilot business unit as a role model for the right business management pattern for KJA businesses. This community service activity aims to help fish cage entrepreneurs in business management through direct examples of similar businesses. The counselling and coaching methods used are demonstrations through direct pilot and informal communication with fostered entrepreneurs. This role model began to be built since 2010, starting from 6 cage units, the business is growing and currently, there are 60 cage units. However, more intensive coaching activities have been carried out since 2012. A total of 5 entrepreneurs were targeted as the main target. As a result of these 5 entrepreneurs, several other entrepreneurs have begun to imitate the business management patterns applied in the role model and they are still able to survive and start a new step in developing the business.